Viral mimicry may help explain immunogenic cell death - Matthew S. Levine; Jiexi Li; Lauren I. R. Ehrlich; Ronald A. DePinho; Brent Iverson; Jonathan L. Sessler (Proceedings of the National Academy of Sciences, 2026)
Viral mimicry may be an underappreciated contributor to chemotherapeutic potency in animal models and patients. This hypothesis is based on studies of a bis-Au(I)-NHC complex that was found to generate a strong anti-tumor immune response in vivo in two different challenge studies using an iKAP colorectal cancer mouse model. RNA profiling of treated cells revealed the stimulation of genes that overlap with those upregulated during a viral infection. The bis-Au(I)-NHC complex generates reactive oxygen species (ROS) through the simultaneous redox cycling of the naphthoquinone moiety and inhibition of thioredoxin reductase with Au(I). This ROS increase causes endoplasmic reticulum stress, activation of the unfolded protein response pathway and upregulation of Ifih1, a gene that encodes for the viral dsRNA sensor MDA5. Activation of MDA5 triggers a strong type I interferon response and expression of chemokine ligand 10 that can recruit immune cells to the treated tumor in a manner analogous to immune responses during viral infection. This proposed mechanism bridges the gap between cytotoxicity and the innate and adaptive immune responses. We suggest viral mimicry may be a key driver of chemotherapy potency in animals and an important determinant of positive outcomes in cancer patients.